2014
DOI: 10.1094/pdis-09-13-0980-re
|View full text |Cite
|
Sign up to set email alerts
|

Response of Fusarium thapsinum to Sorghum brown midrib Lines and to Phenolic Metabolites

Abstract: Sorghum lines were bred for reduced lignin for cellulosic bioenergy uses, through the incorporation of brown midrib (bmr)6 or -12 into two backgrounds (RTx430 and Wheatland) as either single or double-mutant lines. When these lines were assessed for resistance to Fusarium thapsinum stalk rot, a cause of lodging, they were as resistant to F. thapsinum as the near-isogenic wild type. Peduncles of newly identified bmr lines from an ethyl-methanesulfonate-mutagenized population, inoculated with F. thapsinum, were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
45
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 24 publications
(46 citation statements)
references
References 50 publications
1
45
0
Order By: Relevance
“…According to Funnell-Harris et al (2014), one possible effect of changes in phenolics composition in the plant is due to their direct effect on inhibiting pathogens growth. The authors provided in vitro evidence that ferulic acid inhibited several fungi, which could explain the increase of sorghum lines resistance to some diseases (Funnell-Harris et al 2014).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…According to Funnell-Harris et al (2014), one possible effect of changes in phenolics composition in the plant is due to their direct effect on inhibiting pathogens growth. The authors provided in vitro evidence that ferulic acid inhibited several fungi, which could explain the increase of sorghum lines resistance to some diseases (Funnell-Harris et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…According to Funnell-Harris et al (2014), one possible effect of changes in phenolics composition in the plant is due to their direct effect on inhibiting pathogens growth. The authors provided in vitro evidence that ferulic acid inhibited several fungi, which could explain the increase of sorghum lines resistance to some diseases (Funnell-Harris et al 2014). Blodgett and Stanosz (1997) observed that different concentrations of phenolic compounds and monoterpenes of red pine inhibited in vitro the spore germination and mycelial growth of Sphaeropsis sapinea.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, there is evidence that in some cases plants with modified lignin may have greater resistance [97]. One cause of greater disease resistance may be due to the increased amount of ferulic acid compounds in the mutants [32]. Leaves from mature bmr plants were more resistant to corn earworm (Helicoverpa zea (Boddie)) and fall armyworm, both common insect pests, than those of the normal lignin lines, possibly due to increased vanillic acid [28].…”
Section: Sorghumsmentioning
confidence: 99%